2019
DOI: 10.32479/ijeep.8013
|View full text |Cite
|
Sign up to set email alerts
|

Development of Digital Economy in the Energy Industry-Specific Modernization

Abstract: Digitalization of economy defines the extent of possibility in the use of the single information field that could have defined the possibilities for the forecast of the enterprise's activities. The novelty of the study is in the fact that it implements the aspects of the formation of a single forecasting structure for the consumption of the energy sector's production components within a single energy information system. The paper deals with the digitalization of the energy branch based on the approach to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Unlike Baxter (2012), Inshakov et al (2019), Kabeyi and Olanrewaju (2022), Kapitonov et al (2019), Kluczek et al (2021), andRatner et al (2022), it was proved that digitalization of the energy economy based on advanced technologies of Industry 4.0 is not universal-it should be based on a unique organizational model for each category of countries, considering its peculiarities. The reasoning of this conclusion is based on the fundamental differences in the connection of energy sustainability with the readiness for the Frontier Technologies Index and with the government AI Readiness Index among countries of different categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Baxter (2012), Inshakov et al (2019), Kabeyi and Olanrewaju (2022), Kapitonov et al (2019), Kluczek et al (2021), andRatner et al (2022), it was proved that digitalization of the energy economy based on advanced technologies of Industry 4.0 is not universal-it should be based on a unique organizational model for each category of countries, considering its peculiarities. The reasoning of this conclusion is based on the fundamental differences in the connection of energy sustainability with the readiness for the Frontier Technologies Index and with the government AI Readiness Index among countries of different categories.…”
Section: Discussionmentioning
confidence: 99%
“…Maggiore et al (2021), Morelli et al (2022), Wachnik et al (2022), andZaidan et al (2022) indicated that, in order to fully take benefit of the advanced technologies of Industry 4.0 in the energy economy, it is advisable to actively use them by representatives of all interested parties: energy companies, state regulators of the energy economy, and energy consumers. Baxter (2012), Inshakov et al (2019), Kabeyi and Olanrewaju (2022), Kapitonov et al (2019), Kluczek et al (2021), andRatner et al (2022) stated that the digitalization of the energy economy based on advanced technologies of Industry 4.0 is universal-it is suitable for all countries, regardless of their energy efficiency, role, and position in global energy markets. Based on the above publications, it can be concluded that the existing approach to the development of the energy economy based on Industry 4.0 technologies recognizes digitalization as a priority of this development with the secondary sustainability of energy (it is assumed that digitalization provides it).…”
Section: Digital Energetics Based On the Technologies Of Industry 40:...mentioning
confidence: 99%
“…This immediately affects the decline in agricultural production, the deterioration of human health, the increase in mortality, the decline in the birth rate and migration of the population to other places of residence, the deterioration of already difficult demographic indicators in a particular region. This situation is particularly painful for the demographics of Siberia, the Far East, and Kamchatka Territory (Kapitonov et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…All cities in Russia are at different stages of this process, which is largely due to the influence of technological, social, economic, cultural problems, as well as the activity of the population living in them. In the context of the formation of a Humane Smart City in Russia as a human-centered one, interactive interaction of citizens, business structures and the state, represented by certain structural entities, is necessary (Kapitonov et al, 2019).…”
Section: Methodsmentioning
confidence: 99%